The mediating role of creative self-efficacy in the relationship between organizational intelligence and organizational agility of teachers - Abbas Gholtash (مدیریت و چشم انداز آموزش)
The purpose of this research was to explain the mediating role of creative self-efficacy in the relationship between organizational intelligence and organizational agility. This research was applicable in terms of purpose, and correlational in terms of nature and method. The statistical population of this research includes all primary teachers in Sarchehan, whose number was more than 160. Using Morgan's table and stratified random sampling, 113 people were selected as the sample size. The data collection tool was Zhang's organizational agility questionnaire, Karoski's et al,.'s creative self-efficacy, and Albrecht's organizational intelligence questionnaire. To analyze the data, the significance test of Pearson's correlation coefficient and simple regression analysis as well as hierarchical regression by Baron-Kenney method were used. The findings showed that creative self-efficacy can be predicted by organizational intelligence. Organizational agility can be predicted by organizational intelligence. Organizational agility can be predicted by creative self-efficacy. Creative self-efficacy plays a significant mediating role in the relationship between the variables of organizational intelligence and organizational agility.Extended abstractIntroductionAgility is called the organization's ability to face unexpected changes (Akkaya, 2021). There are various variables that make an organization become an agile organization, one of them is self-efficacy, which was first proposed by Bandura. Creative self-efficacy affects the actual power of the person when facing challenges by determining the beliefs of a person about his power to influence situations. Self-efficacy employees can easily hunt environmental opportunities and create an agile organization (Mirzazadeh, 2021). Another variable considered in this research is organizational intelligence. Organizational intelligence refers to the capacity of an organization as a whole to collect information, innovate, produce knowledge and act effectively based on the knowledge it has produced (Af Malmborg, 2021). Despite extensive research in the field of organizational intelligence and organizational agility, there are significant gaps in previous researches. Most of these researches have investigated each of these components separately and paid less attention to the mediating role of creative self-efficacy. Also, few studies have been conducted in the field of primary education, especially in less developed areas such as Sarchehan. This indicates the need for more comprehensive and focused research on the interactions between these components in these specific environments. Investigating these gaps and trying to fill them can lead to a better understanding of how to improve organizational agility by enhancing creative self-efficacy and organizational intelligence. Therefore, the main problem of the present research is raised as follows: Does creative self-efficacy play a mediating role in the relationship between organizational intelligence and organizational agility of elementary school teachers in Sarchehan city? Theoretical frameworkAgilityOrganizational agility refers to a combination of flexibility, agility and speed. This structure is defined as the organization's ability to respond to changes and maximize opportunities (Ridwandono & Subriadi, 2019). An agile organization combines organizational processes and people with up-to-date technology to meet customer needs for providing quality services and products in a short and appropriate time (Tarba et al, 2023). Agile organizations can be influenced by the creative self-efficacy of their employees. Creative self-efficacy is a term that refers to the ability of people to use creativity and innovation in order to achieve goals and solve various problems. This concept includes a combination of two important features, i.e. self-efficacy and creativity. Self-efficacy means believing in one's ability to perform tasks and face challenges, while creativity refers to the ability to generate new ideas and find different solutions to existing problems (Jalali and Heydarifard, 2020). The history of creative self-efficacy dates back recent decades, because during this period, attention to the needs of a dynamic and advanced society and the needs of the labor market has increased more than ever (Puente-Diaz et al, 2024).Creative self-efficacy:The term creative self-efficacy is derived from the term and theoretical context of self-efficacy introduced and defined by Bandura (1997). Bandura defines self-efficacy as "an individual's belief that he can function successfully in a specific environment." Accordingly, we define creative self-efficacy as a person's belief in their ability to produce creative results in a specific environment or in general.Bandura claims that self-efficacy is a strong condition for creative performance, because self-efficacy increases motivation that prioritizes weight and emphasis on one's own thinking and action (Brockhus et al, 2014). Therefore, individual motivation stimulates two aspects; first, choosing a specific behavior; and second, following that type of behavior. There are other concepts with similar meaning, such as self-image, self-esteem and self-confidence. All of these concepts are related to people's overall self-image, but creative self-efficacy differs insofar as it relates to specific creativity self-efficacy, which, we hypothesize, is different from general self-efficacy; a person's overall belief. The ability to successfully cope with the demands of different tasks in different domains was proposed by Shaw et al, (2021). More theoretical considerations about the relationship between self-efficacy and creativity are proposed by Ford [1996], who considers self-efficacy as a key motivational component in his model of defined individual creative action (Karofsky et al, 2016).Organizational intelligence:Organizational intelligence is a new concept in the field of management organization and 21st century literature. Karel Albreckt explained this concept in 2002 in the book Power of Mind at Work. Albrecht defines organizational intelligence as the talent and capacity of an organization in the movement of its mental power and the concentration of this mental power in realizing the mission of the organization. According to Albrecht's law, under the title of group stupidity, it can be stated that organizations, in addition to threatening their competitors and their environment, also move towards harming themselves (Nasabi, 2008). Karl Albrecht, in order to succeed in business, refers to having three factors: smart people, smart teams, and smart organization (Abazari, 2006, p25). In relation to organizational intelligence, different definitions have been proposed by many experts, some of them are mentioned below.Halal considers organizational intelligence to be the result of five subsystems of organizational structure, culture, stakeholder relations, knowledge management, and strategic processes (Halal, 2007).Research methodologyThis research was applicable in terms of purpose, and correlational in terms of nature and method. The statistical population of this research includes all primary teachers in Sarchehan, whose number was more than 160. Using Morgan's table and stratified random sampling, 113 people were selected as the sample size. The data collection tool was Zhang's organizational agility questionnaire, Karoski's et al,.'s creative self-efficacy, and Albrecht's organizational intelligence questionnaire. To analyze the data, the significance test of Pearson's correlation coefficient and simple regression analysis as well as hierarchical regression by Baron-Kenney method were used.Research findingsThe findings showed that creative self-efficacy can be predicted by organizational intelligence. Organizational agility can be predicted by organizational intelligence. Organizational agility can be predicted by creative self-efficacy. Creative self-efficacy plays a significant mediating role in the relationship between the variables of organizational intelligence and organizational agility. The indirect effect of organizational intelligence on organizational agility through creative self-efficacy is 0.118. In fact, with a unit increase in organizational intelligence in the presence of creative self-efficacy, organizational agility increases by 11.8 percent.ConclusionThe findings showed that organizational intelligence has a direct and significant effect on creative self-efficacy. This research finding is in line with the results of Ostvarzabarjadi et al, (2017) and Darabeygi and Eslamieh (2015). In explaining these findings, it can be said that organizational intelligence helps teachers to have a deeper understanding of the organizational environment and the needs of their students. This ability allows them to make quick and effective decisions that lead to increased organizational agility. Also, the findings showed that organizational agility can be predicted by organizational intelligence. This research finding is in line with the results of Perkayti et al, (2023), Kiani et al, (2016), and Shiri et al, (2016). In explaining these findings, it can be said that organizational intelligence includes the organization's ability to collect and analyze information efficiently. These abilities help teachers make better decisions and respond quickly to environmental changes and students' needs. Quick and accurate decision-making processes increase the organizational agility of teachers. Based on the research results, the following practical suggestions are provided:- The creation of working groups and cooperation teams between teachers provides the possibility of exchanging ideas, experiences and creative solutions, and increases creative self-efficacy and organizational agility.- Using new technologies such as robotics, virtual reality, educational websites and educational software can improve educational processes and stimulate teachers' creativity and innovation.